Financial capability, income and psychological wellbeing - Mark Taylor; Stephen Jenkins; Amanda Sacker (University of Essex, Institute for Social and Economic Research (ISER), 2011)
We examine whether financial capability has impacts on psychological health independent of income and financial resources more generally using a nationally representative survey. British Household Panel Survey data are used to construct a measure of financial capability, which we relate to respondents' psychological health using the 12-item General Health Questionnaire. We find that financial capability has significant and substantial effects on psychological health over and above those associated with income and material wellbeing more generally. The sizes of these impacts are considerably larger than those associated with changes in household income. Furthermore having low financial capability exacerbates the psychological costs associated with unemployment and divorce.
Keywords: C23; I32; D14; 330; financial capability; psychological health; wellbeing; panel data; BHPS; Gesundheit; Psychologie; Zufriedenheit; Einkommen; Finanzwissen; Anlageverhalten; Großbritannien